2001
DOI: 10.1209/epl/i2001-00451-1
|View full text |Cite
|
Sign up to set email alerts
|

Resonant tunneling in partially disordered silicon nanostructures

Abstract: Low-temperature vertical carrier transport in layered structures comprised of Si nanocrystals separated in the growth direction by angstrom-thick SiO2 layers exhibits entirely unexpected, well-defined resonances in conductivity. An unusual alternating current (ac) conductivity dependence on frequency and low magnetic field, negative differential conductivity, reproducible N-shaped switching and self-oscillations were observed consistently. The modeled conductivity mechanism is associated with resonant hole tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 25 publications
(29 reference statements)
5
29
0
Order By: Relevance
“…A particular focus has been the study of self-organized structures containing nanometer sized Si and Ge crystals [10] which being compatible with present Si technology have important capabilities for device engineering. Applications include those in optoelectronics, [11] tunneling devices, [12][13][14] and nanocrystal memories [10,15].…”
Section: Introductionmentioning
confidence: 99%
“…A particular focus has been the study of self-organized structures containing nanometer sized Si and Ge crystals [10] which being compatible with present Si technology have important capabilities for device engineering. Applications include those in optoelectronics, [11] tunneling devices, [12][13][14] and nanocrystal memories [10,15].…”
Section: Introductionmentioning
confidence: 99%
“…An optically pumped light emitting device is certainly possible, but an electrically excited LED requires vertical carrier transport through the wide band gap a-SiO 2 barriers. For thin enough barriers such transport via hole tunneling has been observed (74,75), visible LEDs have been demonstrated (50)(51)(52)(53)76,77) and, remarkably, a silicon light-emitting transistor for on-chip optical interconnection has been produced (78). Following a theoretical prediction of a large optical gain in ultra thin silicon quantum wells (79), Saito et al (80) have recently observed optical gain and stimulated emission by current injection into an ultra thin layer of silicon embedded in a resonant optical cavity.…”
Section: Future Prospectsmentioning
confidence: 99%
“…In fact, almost all transport properties, from which the local QD effects could be determined, were derived by using such arrays. [43][44][45][46] While the evidence for SRT is scarce, 46 there is much evidence for TUCB such as from the time dependent I-V characteristics that can be interpreted as due to charging and discharging of the silicon QDs. 44 45 Also, non-linear I-Vs have been previously observed on three dimensional systems in the sandwich configuration 47 Following that we concentrated our work on the connectivity aspect and the macroscopic manifestation of the effects that follow the conduction between the individual QD in systems of Si nanocrystallites that are embedded in a SiO 2 matrix (hereafter the ncs system).…”
Section: Transport and Photoluminescence In Ensembles Of Si Nanocrystmentioning
confidence: 99%